Elatostema magni-auriculatum (Urticaceae), a new species from China - Duan, Lin-Dong; Lin, Yun; An, Mingtai; Bi, Hai-Yan (Bangladesh Journal of Plant Taxonomy, 2015)
Elatostema magni-auriculatum, a new species from Guangxi Zhuangzu Zizhiqu, China is described and illustrated. The species is related to E. myrtillus (Lévl.) Hand.-Mazz., but differs from the latter by stems longitudinally angled, stipules linear-lanceolate, leaf blade obliquely ovate or obliquely ovate-elliptic, and staminate perianth lobes oblong-cymbiform. Bangladesh J. Plant Taxon. 22(1): 4346, 2015 (June)